Zina; Transnational Feminism, and the Moral Regulation of Pakistani Women - Shahnaz Khan (Karachi Oxford University Press, 2006)
The Zina Ordinance is part of the Hadood Ordinances that were promulgated in 1979 by the military dictator General Zia-ul-Haq, a self-proclaimed president of Pakistan. Since then, tens of thousands of Pakistani women have been charged and incarcerated under the ordinance, which governs illicit sex. Although most of these women are subsequently released for lack of evidence, they spend months or years in jail before trial. To date, these laws still remain in effect, despite international calls for their repeal. Over a five-year-period, Shahnaz Khan interviewed women incarcerated under the zina laws in Pakistan. She argues that the zina laws help situate morality within the individual, thus de-emphasizing the prevalence of societal injustice. She also examines the production and reception of knowledge in the west about women in the third world, identifying a productive tension between living in the west and doing research in the third world. She concludes that transnational feminist solidarity can help women identify the linkages between the local and global and challenge oppressive practices internationally. This analysis will appeal to scholars and students of gender, law, human rights, and Islamic/Middle Eastern studies.
Include Notes, References and Index.
Keywords: Feminism--International cooperation -- Fornication (Islamic law) -- Sex discrimination against women -- Women--Social conditions -- Pakistan -- Women (Islamic law) -- Women--Religious aspects--Islam